Prediction of some Tunisian roughages voluntary intake by Noire de Thibar ewes - Rouissi H.; Chermiti A.; Hammami M.; Toukebri H.; Rekik B. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The present study aims at predicting the voluntary intake of different roughages by ewes. Rations based on Egyptian clover (Trifolium alexandrium), oat (Avena sativa), barley (Hordeum vulgare) Souihli, barley Manel, vetch (Vicia sativa)-oat silage, and vetch-oat hay were distributed ad libitum twice a day during different periods of 4 weeks each to 6 black-thibar ewes (age = 4 years and body weight = 57 kg). Ewes' regimen was enriched by 10 g/Kg LW0.75 of concentrate and by 30 g/animal daily of a commercial mixture of minerals and vitamins. Chemical composition (DM, CP, NDF, and CF) was determined for each roughage. Ruminal degradability of these roughages was determined using the technique of nylon bags and was modelled as: Dg = a + b (1-e-ct), where Dg is the ruminal degradability in time t and a, b and c are constants. The CP and NDF contents ranged from 7.6 to 19.1% DM and from 42.0 to 58.3% DM, respectively. For the Dg parameters, the fraction a ranged from 5.2 to 23.5; the fraction b ranged from 51.1 to 71.2 and c ranged from 0.0114 to 0.0570. There were significant differences (p<0.05) among roughages with regard to immediately soluble fraction a, insoluble but degradable fraction b, and fraction rate of degradation c. The voluntary intake of roughages ranged from 784 g DM to 1104 g DM daily. Average silage intakes were 918 g DM daily. This low value may be related to the quality of roughage conservation. Roughage intake can be predicted based on chemical characteristics. The NDF and the CB contents with ruminal degradability parameters explained 34% of the total variation of roughage intake by Black-Thibar ewes (DMI g/Kg LW0.75 = -1470.46 + 5.93 CF + 10.39 NDF + 12.73 NDS + 2.15 a + 2.82 b.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)